Pengaruh Employee Engagement dan Work Engagement terhadap Turnover Intention melalui Kepuasan Kerja sebagai Variabel Intervening - Nisa Rahmawati; Abadiyah, Rifdah; Firdaus, Vera (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2024)
This research aims to examine the influence of employee engagement and work engagement on turnover intention, with job satisfaction as an intervening variable among healthcare workers in hospitals in Sidoarjo. This study employs a descriptive quantitative method. The sampling technique used in this study is purposive sampling, with a total of 100 respondents. Data collection was conducted by distributing questionnaires using a Likert scale. Data analysis was performed using SPSS 25. The results indicate that employee engagement has a negative significant effect on turnover intention. Work engagement has a negative but not significant effect on turnover intention. Employee engagement has a positive and significant effect on job satisfaction. Work engagement has a positive significant effect on job satisfaction. Job satisfaction does meditate the relationship between employee engagement and turnover intention. Job satisfaction does meditate the relationship between work engagement and turnover intention.